2019
DOI: 10.15561/18189172.2019.0403
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of anthropometric measurement and body composition between basketball players from different competitive levels: elite and sub-elite

Abstract: Background and Study Aim: The purpose of this study was to describe anthropometric characteristics and body composition of basketball players from two competitive levels, elite and sub-elite as well as to make a comparison between them. Material and Methods: Fifty-seven male subjects were enrolled in this study, divided into three groups: fourteen elite basketball players, twelve sub-elite basketball players and thirty-one healthy sedentary subjects (subjects from general population). All subjects were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
2
6
0
4
Order By: Relevance
“…According to the results, elite basketball players had more muscle mass and less fat mass than amateurs, which is in line with the findings of previous studies [ 53 , 54 ]. Additionally, we found that elite basketball players had a higher peak power output ( Table 1 and Figure 3 ) with a lower average heart rate ( p < 0.05) and a comparable RPE than amateur basketball players ( p > 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…According to the results, elite basketball players had more muscle mass and less fat mass than amateurs, which is in line with the findings of previous studies [ 53 , 54 ]. Additionally, we found that elite basketball players had a higher peak power output ( Table 1 and Figure 3 ) with a lower average heart rate ( p < 0.05) and a comparable RPE than amateur basketball players ( p > 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…The results support previous investigations indicating a strong difference regarding the body height among basketball players on the one hand and football players and the subjects from the control group that represents general population on the other hand [8,29]. Thus, selection criteria, different types of play and game rules between the football and basketball game can explain the observed difference.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, the shortest players were observed at the amateur level with mean height range from 180 to 195 cm. When mean height was reported according to playing position, guards (183)(184)(185)(186)(187)(188)(189)(190)(191)(192)(193)) were consistently reported as being shorter than forwards (190)(191)(192)(193)(194)(195)(196)(197)(198)(199)(200)(201)(202)), with centres observed as the tallest players (198-214 cm [Fig. 4]).…”
Section: Anthropometric Characteristicsmentioning
confidence: 99%
“…It should be noted that this battery is not an exhaustive list of tests and outcome variables, and basketball researchers and practitioners are recommended to add or remove tests and output variables as they see fit provided their decisions are guided by logic, rationale, and data. It is undeniable that anthropometry is an important consideration for basketball players [10,32,33,[184][185][186][187][188][189][190][191][192]. Thus, the measurement of height, body mass, and wingspan are strongly recommended at the beginning of testing.…”
Section: Practical Recommendations and Considerations For Testing Phy...mentioning
confidence: 99%